Making Sense of Local Climate Change in Rural Tanzania through Knowledge Co-Production. Issue Volume 34:Issues 3(2014) (October 2014) - Shaffer, L. Jen
Shifting climate parameters and their rippling effects through social-ecological systems have altered the abilities of rural households and communities around the world to make livelihood decisions based on traditional ecological knowledge (TEK). National and regional climate services are responding, but the information they provide may not meet local needs or concerns in an accessible format. Previous anthropological research suggests that integrating different knowledge systems to improve climate services, assist in local decision-making, and strengthen climate models remains problematic. To reduce or avoid some of these problems, a participatory, community-based environmental monitoring project was co-developed with residents of four rural Tanzanian communities. A field team brought in equipment and facilitated the training of local monitors, while communities chose the environmental sectors to monitor, collected and analyzed data, and evaluated the results in light of their local TEK. This interaction between scientists and participating community members highlights the value of knowledge co-production in making sense of environmental changes associated with climate that are observed and experienced at the local level. These activities also empowered communities to explore local climate adaptation and policy creation.